2016
DOI: 10.1177/1077801215624790
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Gender Violence and State Failure

Abstract: The concept of state failure has only recently emerged in the political science and legal literature. Although state failure has been used to predict violent conflicts, and all citizens are affected by violence in failed/fragile states, women are especially at risk. Using data from the WomanStats project, this study's findings reveal that the physical security of women is lower in failed/fragile states compared with more sustainable nations. The characteristics of failed states that increase the likelihood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…To create a relative measure of female earned income, the authors of this work calculated the female-to-male income ratio dividing female income by male income. Finally, the percentage of female seats in a national parliament was used as an indicator of women’s political power (Gould & Agnich, 2016). It can be considered a relative measure of women’s economic status as it was measured with the percentage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To create a relative measure of female earned income, the authors of this work calculated the female-to-male income ratio dividing female income by male income. Finally, the percentage of female seats in a national parliament was used as an indicator of women’s political power (Gould & Agnich, 2016). It can be considered a relative measure of women’s economic status as it was measured with the percentage.…”
Section: Methodsmentioning
confidence: 99%
“…First, most researchers assume gender equality is uniformly related to all forms of violence against women, including homicide and rape (Gould & Agnich, 2016), and they have focused solely on one type of victimization in a study. Inconsistent findings among extant works may be partially attributed to their research focus, female homicide or rape victimization.…”
Section: The Present Studymentioning
confidence: 99%
“…As is well documented within the feminist literature, the underlying causes of gender disparities stem from patriarchal power structures that allow men to limit the freedoms of women and control women's sexuality (see, e.g., Farr, 2005;Fauveau & Blanchet, 1989;Gould & Agnich, 2014;Sanday, 1981). Although feminist discussions of gender inequities are salient for the current study, the intersection of Foucault's notion of power and feminism produces the most fecund theoretical underpinning insofar as state failure is concerned.…”
Section: Theoretical Frameworkmentioning
confidence: 95%
“…Adjudicating between these theories is beyond the scope of this article but it is worth highlighting a few theories about gendered violence and the state, as well as black violence in the United States. While the carceral state literature has largely minimized violence, particularly violence against women, there is a body of literature on the relationship between the state and gendered violence (Capaldi, 2012; Gould and Agnich, 2016;). Globally, scholars have found that violence against women is higher in “failed” states—“states that have high levels of violence, internal displacement, warfare […] and do not produce basic protections of citizens’ rights and personal safety” (Gould and Agnich, 2016: 1345).…”
Section: Race and Femicide In The Usamentioning
confidence: 99%
“…While the carceral state literature has largely minimized violence, particularly violence against women, there is a body of literature on the relationship between the state and gendered violence (Capaldi, 2012; Gould and Agnich, 2016;). Globally, scholars have found that violence against women is higher in “failed” states—“states that have high levels of violence, internal displacement, warfare […] and do not produce basic protections of citizens’ rights and personal safety” (Gould and Agnich, 2016: 1345). Moreover, homicide rates appears to be higher in places with low levels of social support provided by the state (Pratt and Godsey, 2003).…”
Section: Race and Femicide In The Usamentioning
confidence: 99%